The potential distribution of Bactrocera dorsalis: Considering phenology and irrigation patterns - Villiers, M. de; Hattingh, V.; Kriticos, D.J.; Brunel, S.; Vayssières, Jean-François; Sinzogan, A.A.C.; Billah, M.K.; Mohamed, S.A.; Mwatawala, M.; Abdelgader, H.; Salah, F.E.; Meyer, M. de (Cambridge University Press, 2016)
Aspecies in the Bactrocera dorsalis (Hendel) complex was detected in Kenya during2003 and classified as Bactrocera invadens Drew, Tsuruta&White.Having spread rapidlythroughout Africa, it threatens agriculture due to crop damage and loss of marketaccess. In a recent revision of the B. dorsalis complex, B. invadens was incorporatedinto the species B. dorsalis. The potential distribution of B. dorsalis has been previouslymodelled. However, previous models were based on presence data and did not incorporateinformation on the seasonal phenology of B. dorsalis, nor on the possibleinfluence that irrigation may have on its distribution. Methyl eugenol-baited trapswere used to collect B. dorsalis in Africa. Seasonal phenology data, measured as flyabundance throughout the year, was related to each location’s climate to infer climatic growth response parameters. These functions were used along with African distributionrecords and development studies to fit the niche model for B. dorsalis, using independentglobal distribution records outside Africa for model validation. Areas atgreatest risk of invasion by B. dorsalis are South and Central America, Mexico, southernmostUSA, parts of the Mediterranean coast, parts of Southern and EasternAustralia and New Zealand’s North Island. Under irrigation, most of Africa andAustralia appear climatically suitable.